AI chatbots: Perspective from practitioners - Tan, Yee Seng *; Yeo, Chien Ing *; Long, Chiau Ming * (MalaysiaKini, 2023)
In a recent advisory paper on the use of generative artificial intelligence (AI) in higher education (bit.ly/mqaai), the Malaysian Qualifications Agency (MQA) provided a comprehensive analysis of the potential benefits, drawbacks, and suggested approaches for higher education providers, academic staff, and students. The letter emphasizes the importance of maintaining academic integrity when utilizing generative AI in order to preserve the standard of education.